Extraordinary optical transmission through titanium nitride-coated microsphere lattice - Gherman, Ana Maria M.; Vladescu, Alina; Kiss, Adrian E.; Farcau, Cosmin (Photonics and nanostructures, 2020)
[Display omitted] •Sputtering 2D microsphere lattices produces nanostructured titanium nitride (TiN) films.•TiN-coated microspheres exhibit the extraordinary optical transmission phenomenon.•Finite element method simulations reveal hybrid photonic-plasmonic modes.•Transmission band is highly tunable across the optical spectrum. Titanium nitride (TiN), one candidate as an alternative plasmonic material, is deposited by the sputtering method on top of a self-assembled polystyrene microsphere lattice. The optical transmission spectra of the TiN-coated microsphere lattice reveal a transmission pass-band attributed to the extraordinary optical transmission phenomenon, known from subwavelength hole arrays in metal films. Simulations by finite element method show the presence of a hybrid mode resulting from coupling of surface plasmons on the TiN film to photonic guided resonance modes in the dielectric microsphere lattice. The crucial role of the microspheres in the transmission process is also evidenced by dedicated simulations. Such hybrid colloidal photonic-plasmonic crystals based on TiN are promising for future plasmonic applications requiring the thermo-mechanical stability of refractory ceramics complemented by a plasmonic efficiency similar to that of gold, but also for extending the range of current applications beyond the use of the classical noble metals gold and silver.